THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL ATTITUDE, ILLUSION OF CONTROL, FINANCIAL EXPERIENCE, AND PARENTAL SOCIALIZATION ON INVESTMENT DECISIONS OF STUDENTS IN MALANG - Shidqiy, Moh. Ilman Rofi'ush; Miranti, Titis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research is motivated by the importance of investment, financial Literacy and other factors that affect students' investment decisions. This study aims to identify the influence of financial Literacy, financial attitudes, Illusion of control, financial Experience, and parental socialization on students' investment decisions in Malang. A deep understanding of these factors is expected to provide insights into developing more effective financial education policies. This study uses a quantitative method with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The research sample consisted of 210 respondents. The sampling technique uses non-probability sampling with the purposive sampling method. The validity of the questionnaire was tested using convergent validity and discriminant validity, while the reliability was tested from the composite reliability and Cronbach's alpha values. Data analysis was done using path coefficient through bootstrapping with the SmartPLS version 3 application.The results of the study show that Financial Literacy and financial attitudes have a very significant influence on students' investment decisions. Other factors, such as the Illusion of control and parental socialization, were also significant, while financial Experience did not significantly influence. These findings emphasize the importance of financial education and parental support in shaping wise investment behaviour among college students. In addition, a particular trend can be seen in the increase in the number of investors from students since the COVID-19 pandemic. This research is expected to provide additional knowledge for readers about the factors that affect students' investment decisions.